From mass vaccination to personalized vaccinology? The COVID-19 case - Andrea Silenzi; Antonio Vitiello; Giovanni Rezza (Istituto Superiore di Sanità, 2023)
In recent times, especially as a result of the experience gained worldwide with the COVID19 pandemic vaccination campaigns, the personalization of vaccination strategies is becoming increasingly important. This does not yet mean bringing precision medicine and genomics approaches into immunization campaigns, but where there is more than one vaccine against the same disease, there is a need to identify criteria for personalizing vaccination. Vaccination strategies based on prescription appropriateness - whenever is possible - can lead to more effective immune response, reduced rates of adverse events, increased public confidence in vaccination and higher vaccination coverage, contributing to a decrease of morbidity and mortality related to preventable diseases.